Fetal R-Wave detection in the ambulatory monitoring of maternal abdominal signal - Mohd Alauddin Mohd Ali,; Crowe, J.A.; Hayes-Gill, B.R. (1995)
An algorithm for the real-time measurement of the fetal and maternal RR intervals from a single-lead abdominal signal has been developed on a low power TMS32010 digital signal processor development system. The algorithm is based on a combination and modification of earlier techniques which have been proposed to perform similar processing. The performance of the algorithm is improved by the incorporation of validation procedures which enable the algorithm to continue operation despite temporary data loss during maternal movement. The reliability of the R-wave detection is determined from information tagged to the measured R-R intervals indicating the signal condition at the time of detection. These tags are then used as a basis for error correction and the measurement of the algorithm performance. The performance achieved from tests on active pregnant women shows the possibility of implementing the above system for ambulatory use